Correlation between Mean Platelet Volume and Procalcitonin in Sepsis Patients - Rama Dhanivita Djamin; Zelly Dia Rofinda; Desywar Desywar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Sepsis is a clinical condition of potentially life-threatening organ dysfunction caused by the host's response to infection. Delayed diagnosis and treatment of sepsis lead to worsening of the disease, which can lead to circulatory collapse, multiple organ failure, and death, therefore accurate and timely diagnosis can prevent death. Procalcitonin (PCT) is the most widely used, studied, and promising marker for the diagnosis of sepsis. Recent studies have shown that procalcitonin plays an important role in the clinical diagnosis of sepsis because it can differentiate sepsis from SIRS. Most studies found an increase in the Mean Platelet Volume (MPV) in septic patients, both neonates, and adults. The MPV value can be used as a parameter to assess the prognosis of septic patients. This cross-sectional analytical study was conducted on 21 septic patients at Dr. M. Djamil Hospital, Padang from January 2020 to April 2021. Mean platelet volume values were determined using an automatic hematology analyzer based on the formula made by the device. Procalcitonin levels were measured using the enzym-linked immunofluorescent assay method. Data were analyzed by Pearson correlation test and p < 0.05 was significant. The mean age of the research subjects was 54 years and the range was 22-77 years. The number of male and female research subjects in this study was almost the same, consisting of 10 male (48%) and 11 female (52%) patients. The average MPV was 10.59(0.56) fL and the median procalcitonin was 9.35(2.08-200) ng/mL. Pearson correlation test showed that MPV was positively correlated with procalcitonin with moderate correlation (r=0.435, p=0.049). There was a moderate positive correlation between MPV and procalcitonin in septic patients.